2023
DOI: 10.7554/elife.88198
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced active and quiet sleep engage non-overlapping transcriptional programs in Drosophila

Abstract: Sleep in mammals is broadly classified into two different categories: rapid eye movement (REM) sleep and slow wave sleep (SWS), and accordingly REM and SWS are thought to achieve a different set of functions. The fruit fly Drosophila melanogaster is increasingly being used as a model to understand sleep functions, although it remains unclear if the fly brain also engages in different kinds of sleep as well. Here, we compare two commonly used approaches for studying sleep experimentally in Drosophila: optogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
2
1
0
Order By: Relevance
“…In addition, the effect observed during induced sleep was only observed in the central channels, whereas the spontaneous sleep effects appear to at least cover the entire hemisphere from center to periphery. This shows that genetically induced sleep in flies can produce notably different electrophysiological signatures than spontaneous sleep, consistent with several previous similar observations ( 12 , 17 , 36 38 ). For the rest of this current study, we focus on spontaneous sleep.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the effect observed during induced sleep was only observed in the central channels, whereas the spontaneous sleep effects appear to at least cover the entire hemisphere from center to periphery. This shows that genetically induced sleep in flies can produce notably different electrophysiological signatures than spontaneous sleep, consistent with several previous similar observations ( 12 , 17 , 36 38 ). For the rest of this current study, we focus on spontaneous sleep.…”
Section: Resultssupporting
confidence: 92%
“…Our multichannel recordings also revealed that changes in sleep physiology are likely to encompass the entire fly brain, from the optic lobes to the central complex. This is consistent with a recent study where we found that experimentally induced “quiet” and active sleep engaged different whole-brain transcriptional programs ( 36 ). That the whole insect brain “sleeps” is also consistent with other studies, although this has not been previously demonstrated using a comprehensive multichannel approach.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation